A Meta-Analysis of Experimental Studies of Attenuated Schistosoma mansoni Vaccines in the Mouse Model - Fukushige, Mizuho; Mitchell, Kate M.; Bourke, Claire D.; Woolhouse, Mark E. J.; Mutapi, Francisca (Frontiers in Immunology, 2015)
Schistosomiasis is a water-borne, parasitic disease of major public health importance. There has been considerable effort for several decades towards the development of a vaccine against the disease. Numerous mouse experimental studies using attenuated Schistosoma mansoni parasites for vaccination have been published since the 1960s. However, to date, there has been no systematic review or meta-analysis of these data. The aim of this study is to identify measurable experimental conditions that affect the level of protection against re-infection with S. mansoni in mice vaccinated with radiation attenuated cercariae. Following a systematic review, a total of 755 observations were extracted from 105 articles (published 1963-2007) meeting the searching criteria. Random effects meta-regression models were used to identify the influential predictors. Three predictors were found to have statistically significant effects on the level of protection from vaccination: increasing numbers of immunizing parasites had a positive effect on fraction of protection whereas increasing radiation dose and time to challenge infection had negative effects. Models showed that the irradiated cercariae vaccine has the potential to achieve protection as high as 78% with a single dose vaccination. This declines slowly over time but remains high for at least 8 months after the last immunization. These findings provide insights into the optimal delivery of attenuated parasite vaccination and into the nature and development of protective vaccine induced immunity against schistosomiasis which may inform the formulation of human vaccines and the predicted duration of protection and thus frequency of booster vaccines.